The Role of Plant Growth-Promoting Bacteria in Metal Phytoremediation - Kong, Zhaoyu; Glick, Bernard R (Advances in microbial physiology, 2017)
Phytoremediation is a promising technology that uses plants and their associated microbes to clean up contaminants from the environment. In recent years, phytoremediation assisted by plant growth-promoting bacteria (PGPB) has been highly touted for cleaning up toxic metals from soil. PGPB include rhizospheric bacteria, endophytic bacteria and the bacteria that facilitate phytoremediation by other means. This review provides information about the traits and mechanisms possessed by PGPB that improve plant metal tolerance and growth, and illustrate mechanisms responsible for plant metal accumulation/translocation in plants. Several recent examples of phytoremediation of metals facilitated by PGPB are reviewed. Although many encouraging results have been reported in the past years, there have also been numerous challenges encountered in phytoremediation in the field. To implement PGPB-assisted phytoremediation of metals in the natural environment, there is also a need to critically assess the ecological effects of PGPB, especially for those nonnative bacteria.